The complexity of the relationship between "dementia" and depression - Michel Bourin (Archives of Depression and Anxiety - Peertechz Publications, 2018)
For a long time researchers and clinicians have been trying to clarify the possible existing relationships between Alzheimer's disease and the depression in the elderly. This article tries to take stock of these complex links. It seems that often depression is clinically confused with apathy.